Mass-luminosity anomalies: Plausible evidence of recent stellar interaction in the extraordinary blue straggler S1082 - Quitral-Pierart, Amanda; Leigh, Nathan; Mathieu, Robert; Latham, David; Sandquist, Eric; Horch, Elliott (Astronomy and Astrophysics, 2025)
Context. We present an observational and theoretical study of the complex stellar system S1082 in the open cluster M67. This system consists of at least four stars: a blue straggler in a 1.07-day eclipsing binary with a main sequence star (binary A) and another blue straggler in a 1185-day orbit with an unknown companion (binary B). Aims. We analyzed observational data to obtain the orbital and stellar parameters of the components of the eclipsing system. We then explored mass transfer and dynamical encounter scenarios that could explain the derived properties of all of the components of S1082. Methods. We combined high-precision photometry from K2 and TESS with archival light curves, new radial-velocity measurements, and speckle imaging to refine the orbital and physical parameters of the system. To explore the formation pathways, we conducted binary evolution simulations with MESA and dynamical scattering experiments with FEWBODY, followed by a tidal evolution modeling procedure. Results. Our revised radial-velocity solutions yield significantly changed dynamical masses for binary A, reducing the tension with the cluster turnoff mass compared to previous studies. Speckle imaging shows two resolved components separated by 390 AU in projection and, in combination with the two spectroscopic orbits, this is suggestive of a hierarchical quadruple configuration. Our results suggest that the two blue stragglers formed separately, with later dynamical encounters assembling the present configuration. This work underscores the importance of stellar dynamics in shaping the evolution of complex stellar systems within cluster environments such as M67.
Keywords: Binary number; Binary star; Blue straggler; Blue stragglers; Cluster (spacecraft); Open clusters and associations: individual: M67; Photometry (optics); Speckle imaging; Star cluster; Stars: individual: S1082; Stellar evolution; Stellar mass; dept.phy